The many ways of saying “pattern” in French medical texts - Band, Karin (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2001)
Abstract“Pattern” occurs in French as an anglicism; however, its meaning and scope of application are more restricted than those of the English term. With few exceptions, there is no one word that could be used as a French equivalent (the “missing word”). As a result, the meanings of “pattern” will need to be translated in other ways. The challenge to the translator working from French is to recognize “pattern” (the «hidden word”) behind the French terms, and restore it as and where required in the target language. This paper gives equivalents of “pattern” found in context-matched French medical texts.